Van de Hongaarse poesta naar Noord-Borneo: De reisjournalen van Ferenc Witti - Bécsi, Gábor (Acta Neerlandica, 2016)
On October 30th 1882, an article appeared in the New York Times about the death of an Austrian explorer on North Borneo who had been an officer of the British North Borneo Company. Later, however, it turned out that this person had been a Hungarian explorer who, after having studied at the Naval Academy of Vienna, joined the Company as an explorer. The present article is a short biography of Ferenc Witti and thus an introduction to the (according to our knowledge) first publication of the two journals that he kept during his first two expeditions on the island before meeting his death during the third one. Ferenc Witti was remembered by his superiors at the society as a devoted and fine explorer who had a keen eye for botanical, geographical and ethnographical peculiarities, which he described in his journals in a rather detailed way. His devotion led however also to his death. He had been warned by more people not to venture further inlands with a small party but he was convinced that his findings would be very useful for the Company so he carried on with his expedition. Today, a mountain range on Borneo bears his name and there is also a memorial Sandakan, which has been erected as a memento for those who lost their lives in the service of the British North Borneo Company. The name of Ferenc Witti is on the top of this memorial.